Opportunities for Excellence Professionalism and the Two-Year College Mathematics Faculty - Neptune, Carolyn F.; American Mathematical Association of Two-Year Colleges ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2001)
The American Mathematical Association of Two-Year Colleges (AMATYC) is the voice of two-year college mathematics in the United States and Canada, and it has more than 40 affiliate organizations in the two countries. The organization is designed to promote professionalism among mathematics faculty at two-year colleges. This AMATYC publication describes the activities and characteristics of professionally active mathematics faculty members. The paper is divided into the following sections: (1) an introduction, which describes goals and background; (2) An Overview of Two-Year Colleges, including Mission, focus on teaching, and student profile; (3) Opportunities for Excellence in the Classroom, discussing professionalism in establishing a learning environment and professionalism in designing learning activities; (4) Opportunities for Excellence beyond the Classroom, which covers professionalism through independent enrichment, within the department, across campus, in the community, and in the mathematics education community; (5) Professionalism and Its Rewards, which explores contributions to student success and to community progress; and (6) an appendix, which includes personal reflections and information about the author. The publication also offers statements from Teaching Excellence Awards winners. (NB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Faculty; College Instruction; College Mathematics; Community Colleges; Faculty Organizations; Mathematical Enrichment; Mathematics; Mathematics Instruction; Outcomes of Education; Professional Associations; Professional Training; Teacher Improvement; Teacher Motivation; Two Year Colleges; American Mathematical Association of Two Year Coll; Reports, Descriptive